Stress-mediated growth determines Escherichia coli division site morphogenesis - Petr Pelech; Paula P. Navarro; Andrea Vettiger; Luke H. Chao; Christoph Allolio (Proceedings of the National Academy of Sciences, 2025)
In order to proliferate, bacteria must remodel their cell wall at the division site. The division process is driven by the enzymatic activity of peptidoglycan synthases and hydrolases around the constricting Z-ring. We introduce a morphoelastic model that correctly reproduces the shape of the division site during the constriction and septation phases of Escherichia coli . In the model, mechanical stress directs the transformation of the bacterial wall. The two constants associated with growth and remodeling respectively are its only adjustable parameters. Different morphologies, corresponding either to mutant or wild type cells, are recovered as a function of the remodeling parameter. In addition, a plausible range for the cell stiffness and turgor pressure was determined by comparing numerical simulations with bacterial cell plasmolysis data.